FORMS OF VIOLENCE AGAINST NEGATIVE SELF-ESTEEM ON FEMALE VICTIMS - Fakhri, Nurfitriany; Savira, Andina Nidya; Daud, Muh; Buchori, Sahril (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Negative self-esteem is one of the effects of female victimization by violence. The manifestations of violence are physical, sexual, and psychological. This study seeks to determine the relationship between various forms of violence and negative self-esteem among female victims in Makassar. This research employs quantitative methods. 350 women who had experienced physical, sexual, or mental violence were the subjects of this study. The scale of violence and the Rosenberg Self-Esteem Scale (RSES) were used as measuring instruments in this study. The Spearman Rho test was utilized to conduct a nonparametric statistical analysis of the data. The results of this study indicate that physical, sexual, and psychological forms of violence have a positive correlation with negative self-esteem in female victims in the city of Makassar (r = 0.299 and p = 0.000; physical: r = 0.128 and p = 0.016; sexual: r = 0.227 and p = 0.000; psychological: r = 0.302 and p = 0.000). This means that the greater the frequency of physical, sexual, and psychological violence, the higher the negative self-esteem of female victims. Psychological violence exerts the greatest influence on negative self-esteem (r=0.300). It is anticipated that the research can serve as a foundation for the treatment of female victims of violence, including the provision of self-esteem-related interventions